Diabetes insipidus in a patient with a highly malignant B-cell lymphoma and stomatitis - Breidert, M.; Schimmelpfennig, C.; Kittner, Th.; Helwig, A.; Ehninger, G. (Experimental and Clinical Endocrinology & Diabetes, 2000)
A 37-year-old male patient with a diffuse pleomorphic B-cell-lymphoma, which has been diagnosed two month earlier with the primary site at the pterygopalatine fossa on both sides with infiltration of the clivus and cavernous sinus was referred to our hospital for continuation of the third course of CHOP chemotherapy.At admission he reported about a recent history of painful swallowing and intermittent substernal chest pain. Alleviation of the pain on swallowing and the chest pain was apparently only possible by drinking 10 to 15 l of cold coca cola throughout the day and night, a regimen that resulted in polyuria. Physical examination revealed extensive thrush stomatitis and soor esophagitis. Despite successful treatment with fluconazole, polydipsia continued unabated. The classic osmotic test of dehydration and exogenous vasopressin revealed hypothalamic diabetes insipidus (DI). Basal hormones and stimulated endocrine function tests of the adenohypophysis were found to be normal. MRI-scan revealed lymphoma infiltration of the neurohypophysis. After the third course of CHOP chemotherapy the patient surprisingly recovered completely from his excessive thirst.The present report shows that clinical disorders such as thrush stomatitis can mask diabetes insipidus caused by an early relapsing lymphoma.
Keywords: Diabetes insipidus; B-cell lymphoma; stomatitis